Ambiguitas Konsep Perlindungan Hukum Terhadap Pekerja Sosial - Adityo, Rayno Dwi (Morality: Jurnal Ilmu Hukum; Vol 8 No 1 (2022): Morality : Jurnal Ilmu Hukum, 2022)
Abstract: Social worker is a profession that belonging to solve a social dysfunction problems. The forms vary according to needs, for example medical personnel, general personnel, psychologists and others. All provisions for the main tasks of the function are inside the regulation of social worker. There was have interesting issue about the legal protection aspect at the regulation such as unsystematic arrangement of language and multiple interpretation on the chapter of the rule. This research is trying to decrypt ambiguity content of social worker legal protection aspect. This types of research use yuridis normative with library approach, for the analyzing technique analytical description. Primery legal materials consist of such UU RI Nomor 14 Tahun 2019 Tentang Pekerja Sosial and other regulations. Secondary legal materials using law book’s, law journal, scientific journal. In addition supported with tertiary data sources kind of electronic media. The result reveal that the sentences structure out of legal protection aspect is not comply with the right standart procedure. Consequently the value of certainty, justice and law benefit potentially difficult to access by social worker when they come in contact with legal problem’s, for the example we can see to law pretection aspect owned by advocat where made clear sentence’s on they regulation. Keyword: social workers, law protection, multiple interpretation